Evaluating the quality of red blood cell concentrates irradiated before or after cryopreservation. Issue 1 (14th November 2019) - Turner, Tracey R.; Lautner, Larissa; Hill, Angela; Howell, Anita; Skeate, Robert; Acker, Jason P.
Abstract : BACKGROUND: Cryopreserved red blood cell concentrates (RCCs) are often required for patients with rare blood groups. Although transfusions from blood relatives are irradiated before transfusion, research has yet to make clear if this is necessary in cryopreserved RCCs. Given insufficient evidence to the contrary, irradiation of cryopreserved RCCs has been recommended, but the effect of irradiation timing is unknown. Therefore, this study was performed to assess the effect of RCC irradiation pre‐ and postcryopreservation on RCC quality. STUDY DESIGN AND METHODS: Nine whole blood units from healthy donors were processed into RCCs using the buffy coat method. ABO‐ and Rh‐matched units were pooled and split into three groups: precryopreservation irradiation (pre‐CIG), postcryopreservation irradiation (post‐CIG), and nonirradiated controls. Hemoglobin, hematocrit, white blood cell (WBC) count, extracellular potassium, mean cell volume, red blood cell (RBC) morphology, and RBC deformability were measured. RESULTS: Extracellular potassium was greater in the irradiated conditions when compared to the nonirradiated controls and was greater in the post‐CIG group when compared to the pre‐CIG group (p < 0.05). WBC counts decreased after cryopreservation in all groups to values lower than the sensitivity of the assay. RBC deformability was greater in the post‐CIG group when compared to the pre‐CIG group and control group. No other significant differences were observed between groups. CONCLUSION: Irradiation of RCCs can be performed pre‐ or postcryopreservation with little effect on the RCC product, as both irradiated groups resulted in RCCs that were comparable to the nonirradiated cryopreserved RCCs.